2006
DOI: 10.1097/01.bcr.0000238085.87863.81
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Patients Lost to Follow-Up in the Burn Injury Rehabilitation Model Systemsʼ Longitudinal Database

Abstract: We sought to identify whether patterns exist in the Burn Injury Rehabilitation Model Systems' database among participants lost to follow-up at 6, 12, or 24 months after injury and to define characteristics that reliably discriminate between persons who are lost to follow-up and those who are not. All participants met the American Burn Association criteria for major burn injury, were 18 years of age or older, received care from one of four burn model systems, and consented to participate in a 2-year prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 30 publications
1
26
1
2
Order By: Relevance
“…First, participant dropout was high, thus lowering confidence in the obtained evidence. The consistently observed high attrition in this population suggests the need to develop novel approaches to retention (40). Second, unmeasured factors such as preburn characteristics (e.g., resilience, personality, coping style, medications and details of acute treatment, formal lifetime and current psychiatric diagnoses and treatments, family psychiatric history) and trauma-related factors (e.g., trauma severity) could affect results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, participant dropout was high, thus lowering confidence in the obtained evidence. The consistently observed high attrition in this population suggests the need to develop novel approaches to retention (40). Second, unmeasured factors such as preburn characteristics (e.g., resilience, personality, coping style, medications and details of acute treatment, formal lifetime and current psychiatric diagnoses and treatments, family psychiatric history) and trauma-related factors (e.g., trauma severity) could affect results.…”
Section: Discussionmentioning
confidence: 99%
“…The allowable period of time to complete the assessment at a given follow-up was defined as starting 1 month before the actual date, and ending 2 months after the actual date. This redundancy was built into the design to attempt to maximize data collection, because problems in this population have historically resulted in excess attrition (problems include frequent address changes due to home/property destruction, loss of job, opportunity elsewhere, avoidance of reminders of the injury and hospitalization, and fear of collection agency contact) (40). During the index hospitalization, the research assistants assessed symptoms of psychological distress during the week before discharge (i.e., baseline).…”
Section: Methodsmentioning
confidence: 99%
“…The rate of dropout in this study corresponds to those of Holavanahalli et al (2006) who described participation rates at 6, 12, and 24 months follow-up time points as reducing over time from 64%, to 54%, and 42% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, large numbers of participants are required to account for attrition rates (Holavanahalli et al, 2006)such as those found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Em nosso estudo, a média de anos de instrução dos participantes foi baixa (Tabela 1). Estudos realizados em outros países como Estados Unidos (FAUERBACH et al, 1999;HOLAVANAHALLI et al, 2006) e Irã (REZAIE et al, 2011) têm mostrado que a queimadura atinge frequentemente populações com baixo nível de instrução.…”
Section: Ribeirão Preto 2010-2011unclassified